Implementation of Congregational-Based Financing through Qardul Hasan Contracts in Microbusiness Development: Case Study at BMT NU Branch in Sumenep City - Fauziyah, Hanifah; Khalida, Nur Diana; Firdaus, Jannatul; Najiatun, Najiatun (Economic Reviews Journal, 2025)
The article titled, "Implementation of Congregational-Based Financing through Qardul Hasan Contracts in Microbusiness Development (A Case Study of Baitul Maal Wa Tamwil NU Sumenep City Branch)," is a qualitative research study aimed at answering questions about the implementation of LASISMA financing through Qardul Hasan contracts and how this financing contributes to the development of microbusinesses of Baitul Maal Wa Tamwil NU Sumenep City Branch. This research utilizes a qualitative approach with a descriptive method. Data collection was carried out through observation and interviews with respondents who are staff members of Baitul Maal Wa Tamwil NU Branch in Sumenep City and LASISMA financing members in Marengan Village. All types of financing at Baitul Maal Wa Tamwil NU Branch in Sumenep City are Sharia-compliant, including LASISMA (Congregational-Based Services) financing through Qardul Hasan contracts. BMT NU Branch in Sumenep City plays a role in supporting the independence of microbusinesses by providing capital assistance to microbusiness operators. In addition to capital support, BMT NU Branch in Sumenep City also offers guidance known as Basic Education (DIKDAS) to equip financing members with the necessary knowledge to develop their businesses. The sources successfully expanded their product offerings, which also increased their incomes. The results of this study indicate that the LASISMA program implementation at Baitul Maal Wa Tamwil NU Branch in Sumenep City is Sharia-compliant. Baitul Maal Wa Tamwil NU implements the LASISMA program with requirements that adhere to the principles and laws of Qardul Hasan financing. BMT NU contributes to the development of businesses in Sumenep City by providing capital assistance and business development guidance, enabling LASISMA program participants to increase their sales turnover.